Colloidal synthesis of Cu–ZnO and Cu@CuNi–ZnO hybrid nanocrystals with controlled morphologies and multifunctional properties. Issue 22 (24th May 2016) - Zeng, Deqian; Gong, Pingyun; Chen, Yuanzhi; Zhang, Qinfu; Xie, Qingshui; Peng, Dong-Liang
Abstract : A solution method that uses the non-noble metal Cu to construct Cu–ZnO hybrid nanocrystals with well-controlled morphologies is presented. Novel Cu@CuNi–ZnO ternary nanocrystals having ferromagnetic/superparamagnetic properties are also prepared. Abstract : Metal–semiconductor hybrid nanocrystals have received extensive attention owing to their multiple functionalities which can find wide technological applications. The utilization of low-cost non-noble metals to construct novel metal–semiconductor hybrid nanocrystals is important and meaningful for their large-scale applications. In this study, a facile solution approach is developed for the synthesis of Cu–ZnO hybrid nanocrystals with well-controlled morphologies, including nanomultipods, core–shell nanoparticles, nanopyramids and core–shell nanowires. In the synthetic strategy, Cu nanocrystals formed in situ serve as seeds for the heterogeneous nucleation and growth of ZnO, and it eventually forms various Cu–ZnO hetero-nanostructures under different reaction conditions. These hybrid nanocrystals possess well-defined and stable heterostructure junctions. The ultraviolet-visible-near infrared spectra reveal morphology-dependent surface plasmon resonance absorption of Cu and the band gap absorption of ZnO. Furthermore, we construct a novel Cu@CuNi–ZnO ternary hetero-nanostructure by incorporating the magnetic metal Ni into the pre-synthesized colloidal Cu nanocrystals. Such hybrid nanocrystals possess a magnetic Cu–Ni intermediate layer between the ZnO shell and the Cu core, and exhibit ferromagnetic/superparamagnetic properties which expand their functionalities. Finally, enhanced photocatalytic activities are observed in the as-prepared non-noble metal–ZnO hybrid nanocrystals. This study not only provides an economical way to prepare high-quality morphology-controlled Cu–ZnO hybrid nanocrystals for potential applications in the fields of photocatalysis and photovoltaic devices, but also opens up new opportunities in designing ternary non-noble metal–semiconductor hybrid nanocrystals with multifunctionalities.